PHYSICAL EDUCATION AND SPORTS IN THE LIFE OF MODERN SOCIETY - Sharipova, Gulnara; Makarova, Yelena; Kramorov, Viktor (SWorldJournal, 2024)
The article discusses the positive effect of physical education and sports. Current objectives are to improve health, instill interest in activities, increase the body’s performance, and prevent various diseases. Sport and physical culture are a multifunc